Multivitamin-Mineral Use Is Associated with Reduced Risk of Cardiovascular Disease Mortality among Women in the United States(1)(2)(3)(4) - Bailey, Regan L (J Nutr, 2015)
Background: Multivitamin-mineral (MVM) products are the most commonly used supplements in the United States, followed by multivitamin (MV) products. Two randomized clinical trials (RCTs) did not show an effect of MVMs or MVs on cardiovascular disease (CVD) mortality; however, no clinical trial data are available for women with MVM supplement use and CVD mortality. Objective: The objective of this research was to examine the association between MVM and MV use and CVD-specific mortality among US adults without CVD. Methods: A nationally representative sample of adults from the restricted data NHANES III (1988–1994; n = 8678; age ≥40 y) were matched with mortality data reported by the National Death Index through 2011 to examine associations between MVM and MV use and CVD mortality by using Cox proportional hazards models, adjusting for multiple potential confounders. Results: We observed no significant association between CVD mortality and users of MVMs or MVs compared with nonusers; however, when users were classified by the reported length of time products were used, a significant association was found with MVM use of >3 y compared with nonusers (HR: 0.65; 95% CI: 0.49, 0.85). This finding was largely driven by the significant association among women (HR: 0.56; 95% CI: 0.37, 0.85) but not men (HR: 0.79; 95% CI: 0.44, 1.42). No significant association was observed for MV products and CVD mortality in fully adjusted models. Conclusions: In this nationally representative data set with detailed information on supplement use and CVD mortality data ∼20 y later, we found an association between MVM use of >3 y and reduced CVD mortality risk for women when models controlled for age, race, education, body mass index, alcohol, aspirin use, serum lipids, blood pressure, and blood glucose/glycated hemoglobin. Our results are consistent with the 1 available RCT in men, indicating no relation with MVM use and CVD mortality.